Problems Facing Libyan Learners of English (Journal of Academic Research, 2018)
Several international English foreign language (EFL) learners often find themselves in a position where, when they attempt to speak English, they have to use their available linguistic resources to overcome their language problems and put their message across despite the gaps in the target language knowledge (Dörnyei 1995). Tarone (1977) Færch and Kasper (1983) and Bialystok (1990) show in their studies that learners avoid, choose and rely on the target language by means of strategies that help them carry out and succeed in communication. Effective strategies used by second and foreign language learners (L2L/FLL) to face such difficulties are called communicative strategies (Faucette 2001).           Within the area of foreign language research, a number of researchers such as Kasper and Kellerman (1997), Cohen (1998), and Rabab’ah (2007) indicate that there is a link between compensatory strategies and language learning. When learners for example, employ a strategy such as appeal for help or ask each other/their teacher for clarification, this leads to feedback which in turn could lead to effective interaction and language development. What is more, Bialystok (1990: 139) argues that despite the fact that language learners normally use the same strategies e.g. communication, cognitive and metacognitive strategies and consistently achieved a sort of meaningful interaction, it is also true that learners differ in implementing these strategies. This could be attributed to differences in language proficiency, communicative ability, and risk taking behaviour. It has been claimed however, that the use these strategies not only enhances language learners' linguistic competence, but also helps them to cope with their communication problems (Cf. Rabab’ah 2005